Respuesta :

Answer:

[tex]f(x)=\frac{3}{2}(\frac{8}{7})^{-x}[/tex]

Step-by-step explanation:

An exponential function of the form [tex]f(x)=a(b)^x[/tex]  will decay if [tex]0\:<\:b\:<\:1[/tex]

This implies that option A will not decay because [tex]\frac{7}{4}\:>\:1[/tex]

Option B will not decay because [tex]f(x)=\frac{2}{3}(\frac{4}{5})^{-x}\implies f(x)=\frac{2}{3}(\frac{5}{4})^{x}[/tex]  which implies that [tex]b=\frac{5}{4}\:>\:1[/tex]

Option C can be rewritten to get: [tex]f(x)=\frac{3}{2}(\frac{8}{7})^{-x}\implies f(x)=\frac{3}{2}(\frac{7}{8})^{x}[/tex]....This exponential function decays.

Option D will not decay because [tex]-\frac{9}{2}\:<\:0[/tex]

73049

Answer:

Step-by-step explanation:

An exponential function of the form   will decay if

This implies that option A will not decay because

Option B will not decay because   which implies that

Option C can be rewritten to get: ....This exponential function decays.

Option D will not decay because

Step-by-step explanation: